House Sales Promotion Application Using Android-Based Augmented Reality Technology - Saputra, Cahnur; Taurusta, Cindy; Azinar, Azmuri Wahyu (LPPM Institut Teknologi Telkom Purwokerto, 2025)
Augmented Reality (AR) is a technology in the field of multimedia that integrates 3D objects into real-world environments using a camera as the medium and can also be applied to mobile Android devices to enhance interactivity and visualization. This research was conducted due to shortcomings or issues in house marketing, namely the lack of detailed information about the rooms in the houses being promoted. This occurs because brochures only display the exterior of the house and are still in a 2D format. Additionally, prospective buyers who live far from the promoted housing area are unable to visit in person and cannot view the interior details of the houses being promoted or sold. Therefore, an application will be developed to visualize both the exterior and interior designs in 3D by implementing Augmented Reality technology. This is expected to make the house sales promotion for the housing area more realistic and interactive. Additionally, prospective buyers can view the exterior and interior designs of the house realistically, even without visiting the housing location directly. The house sales promotion application using Augmented Reality technology requires a camera as an input device. The application tracks and detects flat objects as markers, and after pressing the